The Effect of Supportive Leadership, Learning Culture, and Responsibility on Job Performance of Teacher in Junior High Schools of South Tangerang - Simorangkir, Sahat T; Karnati, Neti; Abdullah, Thamrin (Universitas Malikussaleh, 2019)
The objective of this research was to determine the effect of supportive leadership, learning culture, and responsibility to job job performance of teacher’s in South Tangerang. The research was conducted by using a survey method with path analysis applied on testing hypothesis. The target population size of this research is 454 of teachers. Research samples selected as much as 213 teachers using simple random sampling technique. Based on this research of data obtained the following conclusions: (1) the supportive leadership has positive direct effect to job job performance, (2) the learning culture as positive direct effect to job job performance, (3) responsibility has positive direct effect to job job performance, (4) the supportive leadership has positive direct effect to responsibility,(5) learning culture have positive direct effect to responsibility, (6) the supportive leadership has positive direct effect to learning culture. The conclusion is that the teacher’s job job performance is effected by the supportive leadership, learning culture, and teacher’s responsibility.